The Effect of Straight Leg Raise Exercise with Static Bicycles on Increasing Quadriceps Muscle Strength in Knee Osteoarthritis Patients - Endang Mien Mas’ud; Hasbiah Hasbiah; Hendrik Hendrik (Humanistic Network for Science and Technology (HNST), 2021)
Knee osteoarthritis is a degenerative disease characterized by pain and limited motion of the joints resulting in muscle weakness. Late consequences can lead to limited motion and shortening of intra and extra joint components. This study aimed to analyze the effect of straight leg raise and static bicycles on the increase in quadriceps muscle strength in patients with knee osteoarthritis. This study was an experimental study with a two-group pretest-posttest design. The research was conducted at the Salewangan Maros Hospital. The population was knee joint osteoarthritis patients aged 40-60 years and experienced quadriceps muscle weakness. The sample met the inclusion criteria obtained by simple random sampling technique so that sample size was 28 subjects, then randomized into two treatment groups, each of 14 subjects. The research data was the strength of the quadriceps muscles using manual muscle testing which was done twice, namely before and after the straight leg raise exercise with a static bicycle. Because the data distribution were not normal, the nonparametric analysis was used. The results of the Wilcoxon test analysis showed that there was a significant effect of giving straight leg raise (p = 0.002) and static bicycles (p = 0.005) training on increasing quadriceps muscle strength. The results of the Mann-Whitney test showed no significant differences between groups on the increase in quadriceps muscle strength (p = 0.481). The results showed that straight leg raises and static bicycles increased muscle strength and there was no difference between the two exercises. Keywords: knee osteoarthritis; exercise; muscle strength, static bicycle; straight leg raise